Revoking Of Civil Servants' Voting Rights Violates The Principles Of Democracy And Human Rights In Indonesia - Parlindungan S, Gokma Toni; Yadewani, Dorris; Saputra, Ronaldo Jus; Putri, Selvi Kurnia; Aisyah, Aisyah (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
The purpose of this study is to assess the impact of revoking State Civil Servants' voting rights (ASN) on the quality of democracy in Indonesia. This study employs a normative research method, drawing on primary legal materials such as the 1945 Constitution, the General Election Law, and the International Convention on the Protection of Human Rights, as well as secondary legal materials such as books, articles, scientific works, or research findings relevant to the subject of study. The findings of this study show that revoking ASN voting rights is an undemocratic action that harms the interests of the entire community because it is fundamentally contrary to democratic principles, violates constitutional provisions, and restricts citizens' political rights. To improve this situation, it is recommended that the government evaluate the policy and consider restoring ASN voting rights, as well as formulating a more effective mechanism to maintain bureaucratic neutrality.